O circuito bregueiro de Belém do Pará: compreendendo a dimensão ocupacional dos Bailes da Saudade - Coelho, Flávia dos Santos (2022)
In the city of Belém do Pará, Brega music parties find a privileged scenario of artistic expression, carrying with them different meanings, as such: affective memories linked to leisure, sociability networks between family and friends and to the daily practices of the popular classes that involve the Brega genre, among others, but which are socially stigmatized. These parties are routinely held in the city of Belém by several main characters, 3 of which are best known: the DJ's, the Bregueiros (producers) and the Festeiros (partygoers). The social stigmas attributed to the party’s participants are mainly linked to derogatory notions that refer to bad aesthetic taste and ways of living perceived as inferior, which can be motivated by hegemonically imposed cultural standards. This work focuses on the Baile da Saudade. The objective of this research was to identify the meanings of engaging of/in the Baile da Saudade parties in the city of Belém do Pará and describing the dynamics of the Brega circuit. Occupational Science contributed to the understanding of this phenomenon, through the detailing of the collective occupational dimension present in the parties. The research, of a qualitative nature, was inspired by an ethnographic approach, was carried out with 5 participants, being 1 DJ, 2 partygoers and 2 producers. The data generation was done through semi-structured interviews and the Photovoice. Both resources were analyzed using Thematic Analysis. The study revealed the constraints, tensions, and opportunities of engaging of/in the Baile da Saudade parties, as a collective occupation, as well as yielded the reflection on theoretical-practical elements in the field of Occupational Science and Occupational Therapy, notably in the Culture field.